The Influence Of Fundamental Factors To Liquidity Risk On Banking Industry: Comparative Study between Islamic Bank and Conventional Bank In Indonesia - Harjum Muharam; Hasna Penta Kurnia (Conference In Business, Accounting, And Management (CBAM), 2012)
Bank and risk are two things that cannot be separated from each other. Both conventional and Islamic banks are more or less similar in risk summary. One of the critical risk is liquidity risk that caused by bank disabilities on meeting their maturity dates of depositors. Therefore it needs further observations to control their liquidity risk. This study investigates the influence of CAR, profitability ratios, NIM, liquidity gaps, and RLA belongs to liquidity risk on banking industry. The population of this study consists of conventional and Islamic banks. The selection of samples uses purposive sampling method. The samples are divided into 3 conventional banks and 3 Islamic banks. The study is based on secondary data in a period of five years, i.e. 2007-2011. The statistical analysis of secondary data has been divided into three, which are descriptive, regressionand hypothesis testing. The study finds negative and significant influence of CAR and ROE to liquidity risk on conventional banks, while ROA and RLA have positive and insignificant effect. In Islamic banks, the research finds positive and significant impact of NIM and ROE to dependent variable, whereas liquidity gaps and RLA have insignificant affect. Liquidity gaps have positive and significant effect to liquidity risk in conventional banks, while ROA has positive direction in Islamic banks. In addition, NIM in first model and CAR in second model is found to be negative and insignificant at 5% significance level.Keywords: conventional banks, Islamic banks, liquidity risk, fundamental factors